Pembuatan Direktori Sulaman Bayang di Kabupaten Pesisir Selatan - Utary, Andini; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractIn this paper, we will discuss about directory of Bayang Sulaman in South Pesisir regency. The purpose of the paper is to describe the process of making Bayang Sulaman in South Pesisir regency. This is done to make us easier to find information about collective motive Bayang Sulaman that we can find in Barung-Barung Belantai Koto XI district South Pesisir regency. We us describtive methodoly which is done by doing observasion, interview and collecting the data from the real source.Based on data analysis we can conclude that the items of making Bayang Sulaman in Pesisir Selatan district are: (1) The name of the product, (2) The name of Bayang Sulaman Motive, (3) The characteristic of Bayang Sulaman, (4) The material which is used in Bayang Sulaman, (5) The aids which is used in making Bayang Sulaman, (6)Adress of Sulaman Bayang, (7) the price of Bayang Sulaman, (8) the photo collection of Bayang Sulaman. The making of Bayang Sulaman is Started by: (1) collection the data, (2) typing the Data inÂ Microsoft Word, (3) arrange the Data collection of Bayang Sulaman. The are some problems in making Bayang Sulaman Directory: (1) In the manufacture of Sulaman Bayang products, (2) The name of the motif is Sulaman Bayang, the writer found thatÂ there were Indonesia and Minang languangages(Regional lengaguage). So to solve that problem, there are several thing that should be done: (1) making this Sulaman Bayang product, the writer must be able to set the time for this Sulaman Bayang product, and short the authors Sulaman Bayang motif name requires accuracy. Â (2) if the name or of the motif uses Minang language (regional languange) in accord with the name of the motif made by owner of the Sulaman Baayang shop. The purpose of using this Minang language to preserve Minang language.Keyword: directory; Bayang Sulaman; South Pesisir regency